Representation of Gender Ideology in Indonesian Novels: The study of the Reformation Era Novel - Yulianesta, Yulianesta (Elite : English and Literature Journal, 2014)
Abstract This article is based on a phenomenon that gender ideology practiced by a society may be reflected on the production of literary work. Thus, even though a novel known as an imaginative work,its content and its gender ideology cannot be detached from social reality. This writing aims to describe (1) role and gender identity (2) women struggle and her relationshipwith other characters, (3) types of gender ideology, (4) Gender inequality, and (5) the relationship gender issues and Indonesia novel produced during reformation era. Gramsci’s theory on hegemony and gender perspective helps describing those five problems presented in this article. The object formal of this research is gender ideology presented in six novels written by Indonesian authors during reformation era. Meanwhile, the material object of the research consists of six novels produced in Indonesia during the reformation era and written by Indonesian. The research found that the six novels represent patriarchal ideology, familiasme ideology, ibuism ideology, and general gender ideology. The four gender ideologies createdomestication of the position and the role of women. The existence and the organization of the gender ideology are supported by masculine hegemony in Indonesian culture. Therefore according to Gramsci, new hegemony should be constructed opposed to those capitalist one. The creation of new hegemony must be constructed on the basis of alteration of consciousness, thnking patterns, perception of world conception, as well as their moral norm. This can be done through education. Besides that, the six authors can be termed as intellectual organics who offers new ideology to deconstruct old hegemonic ideology.